Association between clinical competency and patient’s satisfaction from nursing care - Ghalje, M; Ghaljae, F; mazlum, A (Advances in Nursing & Midwifery, 2009)
Background Quality care has always been the concern of nursing managers. Characteristics of care givers may affect on the quality. On the other hand, clients’ views in this regard is considered as a quality measure. Purpose This descriptive correlational study was conducted to determine the relationship between clinical competency and patient’s satisfaction from nursing care in hospitals affiliated to Zahedan Medical University. Methods 47 nurses and 141 patients were randomly selected. The nurses provided direct care to 3 patients at least for 3 days. The patients were asked on discharge. A questionnaire was used for demographic data collection and completed by interview. Another tool was used for measuring clinical competency with 62 questions regarding managerial, professional, communicational and educational skills, which was applied by head nurses, supervisors, and researchers. Patients’ satisfaction was measured by a 37-item questionnaire concerning physiologic, security and social needs completed by interview. Different statistical tests were used for data analysis. Results Mean age of nurses and patients were 37.3±10.7 and 30.7±4.9 respectively. 74.5% of nurses as well as 53.2% of patients were female. Clinical competency of 17%, 75.5% and 25.5% of nurses was less than expected, in the expected range and more than expected respectively. 9.2%, 61% and 29.8% of patients were dissatisfied, relatively satisfied and completely satisfied with nursing care. Regression test showed a significant, linear and positive correlation between clinical competence and patient satisfaction. Two-way ANOWA showed a significant relationship between clinical competence, sex, education as well as marital status of patients and their satisfaction. Conclusion It seems that the more the clinical competency is, the more the quality care would be and this results in increased patient satisfaction. Therefore, by increasing clinical competence or applying more competent nurses, healthcare system can provide more satisfaction for the clients. Keywords: Clinical competence, Patients’ satisfaction, Nursing care.